Determining how to increase premium honey smoked turkey’s selling potential based on flavor reformulation - Coleman, Derrick T. (Kansas State University, 2013)
Under the leadership of the Van Eekeren family, Land O’ Frost has become one of the fastest growing meat processing manufacturers in the United States. “Premium” is Land O’ Frost’s flagship brand which makes up 57% of the company’s total sales dollars. Of the line of Premium lunchmeats, Honey Smoked Turkey is ranked #3 in total sales dollars. However, if you rank the product’s performance by dividing its all commodity volume (ACV) by the number of pounds sold, it is ranked #7 out of the nine single pack flavors offered in retail. There has been internal speculation that the Honey Smoked Turkey’s sales performance is related to a lack of honey/sweetness flavor in the lunchmeat. As a result, Land O’ Frost needed to determine if the current level of honey/sweetness flavor of the Honey Smoked Turkey needs to be increased in order to stimulate higher growth in sales. A third party consultant conducted a consumer test between Land O’ Frost’s honey smoked turkey and their top two competitors’ honey smoked turkey. Based on the results, the Land O’ Frost product was the least likely preferred and was rated as having the lowest sweetness flavor profile among the three products. In an effort to develop a sweeter tasting honey turkey, different test formulations were developed using different honeys, levels of honey and sweeteners. The lighter the honey grade the less flavor impact was present in the turkey. As a result, a test formula containing twice the amount of light amber honey and the maximum amount of sugar was developed to be sweeter and to offer better marketing claims to potentially attract more customers. Due to product process differences between the Land O’ Frost’s honey smoked turkey and its competitor’s, the decision was made to conduct another consumer test between the current control and the newly formulated test product. The data determined that there was not a significant difference between the two products tested. A triangle test was conducted via a third party and it also confirmed the same conclusion. With the test formula having a slightly higher cost per pound than the current control formula, it was decided internally that the test formula could replace the current formula if the test formula price per pound can be adjusted to the same cost as the control. I would recommend that the level of sugar in the new test formula be slightly decreased until the formula cost per pound is the same as the control. The cost of meat raw materials used by Land O’ Frost often changes due to market price conditions. The new formulated honey smoked turkey’s selling potential would still have a positive impact by utilizing claims such as “double the honey” and “lower sodium” on the package. In this case, the selling potential increase would be more heavily executed from a marketing perspective than from flavor development.
Keywords: Consumer preferences; Land O Frost; Turkey; Economics, Agricultural (0503)